2017
DOI: 10.20471/acc.2017.56.04.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Size of the Left Atriumo Sustained Sinus Rhythm in Patients Undergoing Mitral Valve Surgery and Concomitant Bipolar Radiofrequency Ablation for Atrial Fibrillation

Abstract: Atrial fibrillation is associated with systemic embolization and complications due to anticoagulant therapy. Radiofrequency ablation has been established as an effective and safe method for the treatment of atrial fibrillation. The aim of this study was to evaluate the effect of the size of the left atrium on the outcome of surgical radiofrequency ablation. Forty patients scheduled for elective mitral valve surgery and radiofrequency ablation were enrolled in the study. Group 1 consisted of patients with a lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…We address all adult cardiac and major vascular pathologies (with exceptions such as long-term mechanical support for heart failure and transplantation activities). Our current surgical portfolio includes surgery for ischemic heart diseases (with or without cardiopulmonary bypass, multiarterial grafting, minimally invasive myocardial revascularization [ 3 , 4 ] and surgical treatment of complications, such as ventricular septal defects, myocardial ruptures and left ventricular aneurysms), aortic valve replacement with mechanical or stented bioprostheses, aortic valve repair and valve-sparing aortic root replacement (both reimplantation and remodelling with external annuloplasty) [ 5 ], minimally invasive aortic [ 6 ] and mitral valve surgery [ 7 , 8 ], mitral valve repair and replacement [ 9 ], surgical treatment of any heart valve endocarditis, surgery for tricuspid or pulmonary valve disease, aortic surgery (aortic dissection, ascending and arch aneurysms including the frozen elephant trunk procedure [ 10 ], trauma to the great vessels), surgery for atrial fibrillation [ 11 ], pericardiectomy, surgery for cardiac neoplasms, temporary mechanical circulatory support (intra-aortic balloon pump, extracorporeal membrane oxygenation) [ 12 , 13 ] and carotid endarterectomy. In addition, we provide surgical assistance and standby for various interventional cardiological (percutaneous coronary interventions, transcatheter aortic valve implantations [ 14 , 15 ], interventional treatment for atrial and ventricular arrhythmias) or radiological (thoracic endovascular aortic repair) procedures.…”
Section: Current Position As a Regional Centermentioning
confidence: 99%
“…We address all adult cardiac and major vascular pathologies (with exceptions such as long-term mechanical support for heart failure and transplantation activities). Our current surgical portfolio includes surgery for ischemic heart diseases (with or without cardiopulmonary bypass, multiarterial grafting, minimally invasive myocardial revascularization [ 3 , 4 ] and surgical treatment of complications, such as ventricular septal defects, myocardial ruptures and left ventricular aneurysms), aortic valve replacement with mechanical or stented bioprostheses, aortic valve repair and valve-sparing aortic root replacement (both reimplantation and remodelling with external annuloplasty) [ 5 ], minimally invasive aortic [ 6 ] and mitral valve surgery [ 7 , 8 ], mitral valve repair and replacement [ 9 ], surgical treatment of any heart valve endocarditis, surgery for tricuspid or pulmonary valve disease, aortic surgery (aortic dissection, ascending and arch aneurysms including the frozen elephant trunk procedure [ 10 ], trauma to the great vessels), surgery for atrial fibrillation [ 11 ], pericardiectomy, surgery for cardiac neoplasms, temporary mechanical circulatory support (intra-aortic balloon pump, extracorporeal membrane oxygenation) [ 12 , 13 ] and carotid endarterectomy. In addition, we provide surgical assistance and standby for various interventional cardiological (percutaneous coronary interventions, transcatheter aortic valve implantations [ 14 , 15 ], interventional treatment for atrial and ventricular arrhythmias) or radiological (thoracic endovascular aortic repair) procedures.…”
Section: Current Position As a Regional Centermentioning
confidence: 99%
“…Furthermore, previous studies have shown that the left atrium diameter (LAD) was an important prognostic factor for patients received mitral valve surgery and AFRA with conflicting findings. The prognosis of patients with different LAD is likely to be discrepant ( 5 - 7 ).…”
Section: Introductionmentioning
confidence: 99%